KORELASI KETERAMPILAN MEMBACA APRESIATIF DENGAN KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI MAN 3 PADANG - Saimah, Tsani; Basri, Irfani (Universitas Negeri Padang, 2019)
ABSTRACT This article is written to describe the correlation of the apreciprocative reading skills with the writing skills of the short-text student class XI MAN 3 Padang. This type of research is quantitative with descriptive methods and correlational design. This research sample amounted to 49 people. This research data is in the form of scores of apreciprocative reading skills tests and scores of test-writing skills for short-story text. The data, obtained through two types of tests, is an objective test to measure the test of apresiative reading skills and test performance to measure the writing skills of short story text. Based on data analysis and discussion, the following three things are concluded. First, the skill of reading the appreciative of class XI MAN students 3 Padang is in good qualification (78.81). Secondly, the writing skills of the text of the student's class XI MAN 3 Padang is in good qualification (81.04). Thirdly, there is a significant connection between the apresiative reading skills with the writing skills of the short-text short story at a significantly 95% level with dk = n-1. Based on the results of the research and analysis of data, it was concluded that there is a significant link between the reading skills of the appreciative with the writing skills of the text students of Class XI MAN 3 Padang because thitung > ttabel is 3.12 > 1.67. In other words, to write short story text is required apresiative reading skill.Kata kunci: Korelasi, Membaca, Menulis, Teks Cerpen